Manner Verb Construction and Reduplication of Kedang Language: A Typological Study * - Nurul Khasanah; Agus Subiyanto (PAROLE: Journal of Linguistics and Education, 2020)
This study discusses manner verb construction and reduplication of the Kedang language from the perspective of typology. This study is a descriptive qualitative study by describing the pattern of manner verb construction of the Kedang language. The data is analyzed by using distributional (agih) and identity (padan) methods through breaking down words and sentences. The choice and equivalent of sentences are adjusted with the typology rule of universal language by Dixon (2006); serial verb construction. The result of this study showed that the manner verb construction of the Kedang language is an action-manner with verb and reduplication. There are five patterns of manner verb construction; V1 Intransitive + V2 transitive, V1 Intransitive + V2 Intransitive, V1 Transitive + V1 Transitive, V1 transitive + V2 Intransitive, and V Tran/Inf +Adj. However, manner verb construction with reduplication is classified into three categories: V1 intransitive + total reduplication, V1 transitive + total reduplication, and V1 transitive/intransitive + total reduplication with sound change. The verbs that accompany the reduplication of the word are motion and action verb. The manner verb is always in second place to clarify the activity of the first verb.